1998
DOI: 10.1021/np970383n
|View full text |Cite
|
Sign up to set email alerts
|

An A-Type Proanthocyanidin from Prunus armeniaca

Abstract: Roots of Prunus armeniaca yielded a new A-type proanthocyanidin whose structure was assigned as ent-epiafzelechin-3-O-p-hydroxybenzoate-(4alpha-->8, 2alpha-->O-->7)-epiafzelechin (1). The structure of 1 was determined through extensive 1D and 2D NMR studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…A new A-type proanthocyanidin was isolated from the roots of P. armeniaca and its structure was assigned as ent-epiafzelechin-3-O-phydroxybenzoate-(4α → 8, 2α → O → 7)-epiafzelechin (Prasad et al, 1998). Later on, structures of three isomeric A-type proanthocyanidins isolated from the roots of P. armeniaca were elucidated as entepiafzelechin-(4α → 8, 2α → O → 7)-epiafzelechin (mahuannin A), ent-epiafzelechin-(4α → 8, 2α → O → 7)-(+)-afzelechin, and entepiafzelechin-(4α → 8, 2α → O→)-(−)-afzelechin (Rawat, Prasad, Joshi, & Pant, 1999).…”
Section: Polyphenolsmentioning
confidence: 99%
“…A new A-type proanthocyanidin was isolated from the roots of P. armeniaca and its structure was assigned as ent-epiafzelechin-3-O-phydroxybenzoate-(4α → 8, 2α → O → 7)-epiafzelechin (Prasad et al, 1998). Later on, structures of three isomeric A-type proanthocyanidins isolated from the roots of P. armeniaca were elucidated as entepiafzelechin-(4α → 8, 2α → O → 7)-epiafzelechin (mahuannin A), ent-epiafzelechin-(4α → 8, 2α → O → 7)-(+)-afzelechin, and entepiafzelechin-(4α → 8, 2α → O→)-(−)-afzelechin (Rawat, Prasad, Joshi, & Pant, 1999).…”
Section: Polyphenolsmentioning
confidence: 99%
“…The plant is a rich source of carbohydrates (both mono and polysaccharides) , polyphenols (Socher et al, 2010;Turans et al, 2007), carotenoids (ß carotene) (Ruiz et al, 2005), vitamins C and K, thiamine, niacin, iron, organic acids, phenols and volatile compounds, benzaldehyde, esters, norisoprenoids and terpenoids (Prasad et al, 1998;Mandal et al, 2007).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Organic acids, phenols, volatile compounds, esters, terpenoids have also been isolated 11 . Prunus armeniaca kernels contain a substantial amount of dietary protein 12 along with significant amounts of oil and fiber 13 . In a previous study, 14 reported that sweet Prunus armeniaca kernels contain more oil than bitter kernels and that oleic acid and linoleic acid correspond to approximately 92 g/100 g of the total fatty acids present.…”
mentioning
confidence: 99%